Federal Democratic Republic of Ethiopia : Evaluation of MDGs Specific Purpose Grant to Regions - World Bank (World Bank, Washington, DC, 2016)
Ethiopia is a highly decentralized country. Presently, sub-national government taxes and revenues account for about 28 percent of general taxes and revenues, and sub-national expenditures amount to 51 percent of general government expenditures. The ensuing vertical mismatch is bridged by grants from the Federal government to the regions. Presently, these grants account for 57 percent of sub-national expenditures1. For many years, these grants consisted mostly of a block grant (the Federal General Purpose Grant) given without any strings attached, which means the regions could use it as they wished. The rest of the report is organized as follows. Section two provides the policy context that is the information, data, evolutions, etc. specific to Ethiopia, which are necessary to understand and interpret the MDGs grant policy. Section three present and discusses the policy content that is the components of the policy previously identified. Section four is a policy assessment, which utilizes the evaluation framework proposed above to analyze the relationships between the various components of the policy, and discuss its efficiency, its effectiveness and its success. Section five is a conclusion that summarizes the analysis, and attempts, prudently and modestly, to outline some potential avenues for future action.